Metaphors and cultural narratives on adaptive responses to severe adversity: A field study among the Indigenous Pitaguary community in Brazil. (April 2020) - Meili, Iara; Heim, Eva; Pelosi, Ana C; Maercker, Andreas
The expressions resilience and posttraumatic growth represent metaphorical concepts that are typically found in Euro-American contexts. Metaphors of severe adversity or trauma and the expressions of overcoming it vary across cultures—a lacuna, which has not been given much attention in the literature so far. This study aimed to explore the metaphorical concepts that the Indigenous Pitaguary community in Brazil uses to talk about adaptive and positive responses to severe adversity and to relate them to their socio-cultural context. We carried out 14 semi-structured interviews during field research over a one-month period of fieldwork. The data were explored with systematic metaphor analysis. The core metaphors included images of battle, unity, spirituality, journeys, balance, time, sight, transformation, and development. These metaphors were related to context-specific cultural narratives that underlie the Pitaguary ontological perspective on collectivity, nature, and cosmology. The results suggest that metaphors and cultural narratives can reveal important aspects of a culture's collective mindset. To have a contextualized understanding of expressive nuances is an essential asset to adapt interventions to specific cultures and promote culture-specific healing and recovery processes.